The Effect of Drug Abuse on Youths in Portloko Town, Northern Sierra Leone (Global Journal of Medical Research, 2022)
Drug abuse and addiction have been part of youths in this part of the community in their existing social systems, affecting crime rates, hospitalizations, child abuse, and child neglect, frustration, insane, and disability, HIV /AIDS, Scabies and skin diseases, anaemia, pale in colour. those who take intra venous injections suffer from HIV/aids. Youth nowadays try various drugs so that they feel different from normal, Drugs has become a fashion amongst youth nowadays, both boys and girls are greatly involved in this habit. This paper is presenting the results of the causes, types, effects on the individuals, families, and community as a whole. The different types of drugs taken by youth in these communities were tramadol, pampas, Evostick-, super glue, marijuana, tobacco, pounded tobacco with bicarbonate of soda (snuff), cocaine, petrol, Araldite, kola nut, and alcohol. The factors that lead to the intake of these drugs are as follows, unemployment, lack of effective mentorship, lack of family values, poor parenting guidance, and loss of hope easily assessable, and affordable, peer group influence, cults, secret societies in contributed to youths going into drug This study.